2005
DOI: 10.1097/01.ju.0000158122.16046.68
|View full text |Cite
|
Sign up to set email alerts
|

ACTIVATION OF NATURAL KILLER T CELLS BY Α-Galactosylceramide MEDIATES CLEARANCE OF BACTERIA IN MURINE URINARY TRACT INFECTION

Abstract: These findings suggest a significant role for alpha-GalCer in regulating antibacterial functions by activating natural killer T cells in the murine UTI model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 20 publications
2
10
1
Order By: Relevance
“…J H D mice, lacking both B-1 and B-2 cells (43,212), infected and monitored over a 14-day time period exhibited no significant increase in incidence or severity of cystitis (130). On a final note regarding ILLs, administration of ␣-galactosylceramide (␣-GalCer), a ligand for CD1d-restricted NKT cells, alleviates renal UPEC infection (168). Consistent with this, we have observed a resident population of NK1.…”
Section: Special Operations: Ills In the Innate Immune Response To Upsupporting
confidence: 67%
“…J H D mice, lacking both B-1 and B-2 cells (43,212), infected and monitored over a 14-day time period exhibited no significant increase in incidence or severity of cystitis (130). On a final note regarding ILLs, administration of ␣-galactosylceramide (␣-GalCer), a ligand for CD1d-restricted NKT cells, alleviates renal UPEC infection (168). Consistent with this, we have observed a resident population of NK1.…”
Section: Special Operations: Ills In the Innate Immune Response To Upsupporting
confidence: 67%
“…A significant proportion of hospital cases of sepsis is due to Gram-positive cocci, which induce a different inflammatory response from that of Gram-negative bacteria (25). The function of NKT cells in various milder infections is dependent on the type of infecting agent; thus, NKT cells play a beneficial role in some infections (26,27) and are detrimental in others (11). Therefore, observations from Gram-negative sepsis models cannot be extrapolated to S. aureus sepsis.…”
mentioning
confidence: 91%
“…It was found that the C-glycoside induced more of a Th1 (i.e., IFN-␥) response, was longer lasting, and was actually a better adjuvant than the parental compound itself in murine models of malaria and metastatic melanoma (53)(54)(55)(56)(57). Furthermore, ␣-GalCer administration has been shown to be mostly protective activity against viruses (58 -61), bacteria (62)(63)(64)(65)(66)(67), and other pathogens (68,69). In Trypanosoma cruzi, although GPIs and other lipids from this genus can bind to CD1d, those ligands do not stimulate NKT cells (70).…”
Section: ␣-Galactosylceramide (␣-Galcer) and ␣-Galcer Analogsmentioning
confidence: 99%